Aprendizagem e inovação empresarial em tempos de pandemia da Covid-19 : um estudo na cidade de Sobral/CE/ - Sousa, Mário Antônio Macedo de (My University, 2022)
Contemporary society is going through a turbulent period imposed by the challenges of the Covid-19 pandemic since the beginning of 2020, which has caused suffering, illness and death everywhere. These events greatly impacted the world economy and companies needed to reinvent themselves based on the binomial innovation and learning. This dissertation has the general objective of analyzing how innovations and organizational learning occurred in the context of the pandemic, in the perception of small entrepreneurs from Sobral. To support the research, authors such as: Piret et al. (2021); Antonello and Godoy (2010); Plonski et al. (2017); OECD (2018). The methodological course invested in an exploratory research through a qualitative approach and the interviewees were small businessmen from the city of Sobral-Ce. Data collection was performed through interviews and content analysis proposed by Bardin was used. The research allows us to infer that the pandemic strongly impacted the study participants' businesses, but their resilience made them find survival alternatives. It was observed in the participants' reports that they carried out innovation, but, in the light of the theory adopted in this research, it is not possible to say that there was innovation in any of the investigated cases, however, many innovative actions were found such as: online services, home -office, better qualification of the team, review of processes, adaptation to the new scenario, among others. The presence of informal organizational learning was also identified from the perspective of adaptation as a survival factor for the investigated businesses. [resumo fornecido pelo autor]
A sociedade contemporânea passa por um período turbulento imposto pelos desafios da pandemia da Covid-19 desde início de 2020 que provocou sofrimentos, adoecimentos e mortes por toda parte. Esses eventos impactaram sobremaneira a economia mundial e as empresas precisaram se reinventar a partir do binômio inovação e aprendizagem. Esta dissertação tem como objetivo geral, analisar como as inovações e aprendizagem organizacional ocorreram no contexto da pandemia, na percepção de empreendedores sobralenses de pequeno porte. Para apoiar a pesquisa recorreu-se a autores como: Piret et al. (2021); Antonello e Godoy (2010); Plonski et al. (2017); OCDE (2018). O percurso metodológico investiu em uma pesquisa de caráter exploratório mediante abordagem qualitativa e os entrevistados foram empresários de pequeno porte da cidade de Sobral-Ce. A coleta de dados foi realizada através de entrevista e foi utilizado análise de conteúdo proposto por Bardin. A pesquisa permite inferir que a pandemia impactou fortemente os negócios dos participantes do estudo, mas a resiliência deles os fez encontrar alternativas de sobrevivência. Observou-se nos relatos dos participantes de que realizaram inovação, mas, a luz da teoria adotada nesta pesquisa, não é possível afirmar que houve inovação em nenhum dos casos investigados, no entanto, muitas ações inovadoras foram encontradas tais como: serviços online, home-officce, melhor qualificação da equipe, revisão dos processos, adequação ao novo cenário, dentre outras. Identificou-se também a presença de aprendizagem organizacional informal na perspectiva da adaptação como um fator de sobrevivência dos negócios investigados. [resumo fornecido pelo autor]
Keywords: Aprendizagem organizacional; Desenvolvimento organizacional; Empresas - Sobral (CE); COVID-19; Organizational learning; Organizational change; Business enterprises - Sobral (Brazil)